Thyroid Hormones and Aging: Modulators of Mitochondrial Health, Metabolic Flexibility, and Longevity Pathways - Mazza, Angela D (Hormone and Metabolic Research, 2025)
Thyroid hormones, primarily triiodothyronine (T3) and thyroxine (T4), are critical regulators of metabolic rate, mitochondrial function, and cellular repair mechanisms. Emerging evidence suggests that thyroid status may significantly influence aging trajectories and longevity through modulation of key cellular pathways. This review explores the role of thyroid hormones in aging biology, with a focus on their interaction with longevity-associated signaling pathways and the hallmarks of aging. Both physiological and subclinical thyroid states in the context of healthspan, cognitive preservation, metabolic resilience, and mitochondrial integrity are explored. A narrative synthesis of human and animal studies was conducted, including mechanistic, epidemiologic, and clinical data, to evaluate how thyroid hormone levels affect aging pathways such as mechanistic target of rapamycin, AMP-activated protein kinase, IGF-1, sirtuins, FOXO transcription factors, and mitochondrial biogenesis. Thyroid hormones modulate several hallmarks of aging, including mitochondrial dysfunction, genomic instability, epigenetic drift, and deregulated nutrient sensing. T3 enhances mitochondrial respiration and autophagy while interacting with mechanistic target of rapamycin and AMP-activated protein kinase to regulate energy balance. Altered thyroid function—particularly subclinical hypothyroidism—has been paradoxically associated with increased longevity in some centenarian cohorts, possibly due to reduced oxidative metabolism. However, overt thyroid dysfunction is linked to increased metabolic risk in aging populations. Thyroid hormones serve as metabolic gatekeepers that influence both cellular aging and organismal longevity. A deeper understanding of their role in aging pathways may inform novel strategies for promoting healthy aging, including thyroid hormone modulation and personalized endocrine optimization.
Keywords: thyroid hormone; aging; longevity pathways; integrative endocrinology; mitochondrial function